Branding co-creation with members of online brand communities - Hajli N.; Shanmugam M.; Papagiannidis S.; Zahay D.; Richard M.-O. (Elsevier Inc., 2023)
This article looks at the co-creation of value in the branding process with members of online communities. Three online communities in Iran are analyzed through 45 interviews with members along with three interviews with top managers of the three brands of these communities. A content analysis shows a clear process in that the social interactions of customers in online brand communities with their favorite brands help develop relationship quality and increase customer brand loyalty. The findings suggest that firms may develop their branding strategies using social media and online brand communities through relationship marketing by using an online co-creation strategy. The findings also serve to inform practitioners of the impact of social media on branding and how they can best facilitate these brand relationships. 2016 Elsevier Inc.